Проектна робота як складова інноваційних технологій в процесі навчання іноземної мови - Чижова, Л. І.; Chyzhova, L. I.; ORCID: https://orcid.org/0000-0002-4105-1520 (My University, 2019)
Education is one of the most important spheres of human activity and the determining factor of human development. Many countries around the world have long recognized that the future is behind a civilization that will maximize the development of the intellectual and creative potential of its citizens. Together with science, socio-political institutions, the media and culture, education is an important factor in creating a highly efficient economy, a key tool for civil society formation. In the context of globalization, new geopolitical changes in the world, new tasks are facing education, whose solution is extremely important not only for the education of the future, but also for the development of society as a whole. One of the most important vectors for the development of modern education is the introduction of innovative technologies into education. A necessary condition for the use of information technologies is reforming the education system, developing new didactic and conceptual principles of education. Teaching with innovative technologies qualitatively exceeds classical education. It integrates processes that cannot be combined within classical education: education, employment, career planning, continuing education.
Актуальність даної теми визначає поступову зміну традиційних методів на інноваційні. На сучасному етапі важливим є використання інноваційних технологій та методів навчання при вивчення іноземної мови.
Keywords: Education; globalization; information technologies; teaching; education system; project